Development of Robotic Process Automation for Scraping Prospective Customer Data and Implementation Haversine in PT. XYZ - Novila, Ninna; Emanuel, Andi Wahju Rahardjo; Adithama, Stephanie Pamela (Journal of Information Technology and Computer Science, 2023)
PT XYZ is a finance company that engages in lending. Its activities include branch offices, aiming to increase new customer acquisition. Prospective customer data is required to determine their potential and the location of the nearest branch office. PT. XYZ previously used a third party, but the result was not equal to what was required, and the company was forced to pay to obtain data equal to what was required. Google Maps is a data source that is utilized and freely accessible. This study scraped prospective customer data using robotic process automation. Robotic process automation was developed using UiPath with Google Maps and Plus Codes as data sources. The Haversine method is used to determine the location of the nearest branch office. 595 prospective customer records were obtained through robotic process automation using seven search keywords. The result for 579 prospective customers is correct, but the result for 16 is incorrect. Haversine Method applies to 582 prospective customer records; however, the remaining records lack latitude and longitude, making Haversine Method inapplicable.